Assessing mood state, stress and recovery in endurance runners wearing compression socks - Welman, K.; Venter, R.; Terblanche, E. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Adequate training and recovery are both important factors to enhance endurance performance and to avoid overtraining. Recovery and stress are also dynamic in nature and sport specific (Nicolas et al., 2011). A recent survey reported that compression garments are the most popular recovery intervention amongst endurance athletes (Nusser & Senner, 2010). Still limited scientific evidence support these anecdotal claims. This study set out to investigate distance runners` perception of stress and recovery following an ultramarathon race while wearing compression socks. Methods Psychological states were assessed in 40 runners (42±8years) before and for 72 hours after a 56km race. Participants were men who participated in regular endurance races over the past 3 years. Runners were randomly divided in either an experimental group (CS), wearing knee-high compression socks (20-30mmHg), or a control group (C) wearing knee-high sport socks (<5mmHg). Runners completed the Recovery-Stress-Questionnaire for Athletes (RESTQ-Sport) twice, Stellenbosch Mood Scale (STEMS) five times and five muscle damage and energy level questionnaires. To quantify muscle damage myoglobin (Mgb) was assessed. Results The CS ran 13 minutes faster than the C (P>0.05;ES=0.32). Results revealed significant changes in all variables in both the C and CS after the race, which recovered in both groups by 72 hours. The CS demonstrated less anger at 24 hours after the race (P=0.01;ES=0.58). C were more confident when wearing the control sock compared to the CS (P=0.06), specifically directly after the race (P=0.04;ES=0.49). CS reported 25% and 75% less fatigue directly (P=0.03;ES=0.44) and 48 hours after the race (P=0.03;ES=0.61). Runners wearing control socks stated to have less energy on average compared to the CS (P=0.03). C perceived 37% more total stress at 72 hours after the race compared to CS (P= 0.05;ES=1.97). Even though Mgb was 46% more reduced directly after the race compared to C (P=0.04;ES=0.67), the CS did not perceive a faster recovery rate. Discussion The results suggest that an ultraendurance race induces perceived stress and leads to subsequent changes in perceived recovery. In addition, CS seems to contribute to an improved perception in fatigue, energy levels and reduces stress, but not necessarily improved perception of recovery and confidence. Conclusions This investigation added to our knowledge of the use of compression socks as a recovery technique, which may form part of a balanced training program for optimal performance. In addition, the results give us insight to the psychological challenges of a demanding distance running event.